Evaluation of association studies and meta-analyses of MTHFR gene polymorphisms in colorectal cancer. (March 2015) - Haerian, Batoul Sadat; Haerian, Monir Sadat
There is a discrepancy between the results of 89 original studies and 15 meta-analyses investigating the association of MTHFR rs1801133 and rs1801131 polymorphisms with colorectal cancer (CRC) risk. We examined this hypothesis through meta-analyses of both loci and their diplotypes as well as evaluation of previous meta-analyses. The present meta-analysis showed that rs1801133 and rs1801131 might be CRC susceptibility variants in Americans and Australians and rs1801133 in Brazilians and Japanese. A strong linkage disequilibrium was observed between both loci and their diplotypes were associated with CRC risk. Evaluation of 15 meta-analyses showed a high discrepancy among their findings, mainly caused by population stratification of original studies and data analysis strategies in meta-analysis. Population stratification was more dominant in the studies from Australia, America and Brazil leading to false positive or negative results. In conclusion, these loci alone might modify the development of CRC in some ethnicities.